An auto-generated geometry-based discrete finite element model for damage evolution in composite laminates with arbitrary stacking sequence - Jiakun Liu; Stuart Leigh Phoenix (Composites Part C: Open Access, 2020)
Stiffness degradation and progressive failure of composite laminates are complex processes involving evolution and multi-mode interactions among fiber fractures, intra-ply matrix cracks and inter-ply delaminations. This paper presents a novel finite element model capable of explicitly treating such discrete failures in laminates of random layup. Matching of nodes is guaranteed at potential crack bifurcations to ensure correct displacement jumps near crack tips and explicit load transfer among cracks. The model is entirely geometry-based (no mesh prerequisite) with distinct segments assembled together using surface-based tie constraints, and thus requires no element partitioning or enrichment. Several numerical examples are included to demonstrate the model’s ability to generate results that are in qualitative and quantitative agreement with experimental observations on both damage evolution and tensile strength of specimens. The present model is believed unique in realizing simultaneous and accurate coupling of all three types of failures in laminates having arbitrary ply angles and layup.